Adventure sport tourism in Wales: The role of the Welsh language in cultural identity and economic revitalisation - Bear, Olivia (Studia Celtica Posnaniensia, 2025)
Adventure Sport Tourism (AST) represents a dynamic intersection of outdoor recreation, culture, and language, offering both economic opportunities and pathways for cultural preservation. This chapter examines AST in Wales, focusing on its relationship with the Welsh language as a key cultural and economic asset. Drawing on Wales’ diverse natural landscapes – from the mountains of Eryri to the coastal trails of Pembrokeshire – the discussion explores how both ‘hard’ and ‘soft’ adventure activities can serve as platforms for linguistic and cultural engagement. Despite its rapid growth, AST remains under-researched globally, and particularly within the context of minority or indigenous languages. By analysing the integration of Welsh into tourism services, interpretation, and branding, the chapter identifies AST as a potential driver of linguistic revitalisation and cultural authenticity. It further addresses challenges such as limited Welsh-speaking representation in the sector and perceptions of AST as an exclusive pursuit. Ultimately, the chapter argues that embedding the Welsh language within adventure tourism practices not only strengthens the sector’s identity and competitiveness but also supports broader efforts toward linguistic sustainability and cultural resilience, positioning Wales as both an adventure destination and a model for culturally grounded tourism development.